EVALUASI DAN TINDAK LANJUT KURIKULUM PENDIDIKAN ISLAM - Septhia Eka Novitasari; Khoirul Anam; Asrop Syafi'i (MPI STAI Sangatta Kutai Timur, 2025)
Regular evaluation of the Islamic education curriculum is crucial to ensure the quality, effectiveness, and relevance of learning, particularly in shaping students' character and applying religious values in their daily lives. This journal aims to analyze the basic concepts of Islamic education curriculum evaluation, identify the challenges faced, and formulate necessary follow-up actions. This research uses a descriptive library research method with a content analysis approach. The analysis was conducted by reviewing research results from the most relevant to the least relevant, starting from the newest research year to the oldest. The results show that curriculum evaluation is a systematic and continuous stage to validate and ensure the reliability of data to determine policies related to the curriculum, which includes learning objectives, content, and methods. Challenges in evaluating Islamic education curriculum stem from internal and external factors, including the achievement of eight national education standards, population growth, character education issues, and an inadequate paradigm in understanding the curriculum. As a follow-up, cooperative efforts from stakeholders are needed to produce an integrated curriculum and develop teacher professionalism sustainably, supported by programs such as pre-service education, in-service education, and in-service training. Islamic education curriculum evaluation is essential to ensure the effectiveness and relevance of learning. By addressing challenges through an integrated curriculum and the development of professional educators, it is hoped that students will be formed who are capable of facing the dynamics of the times.